Crecimiento y sobrevivencia en una plantación de Swietenia macrophylla del Ciefor - Puerto Almendra, Loreto – perú. 2022 - Muñoz Arevalo, Andy Christian (2023)
The present investigation was carried out in plantation No. 10 of Swietenia macrophylla (Caoba) with the objective of determining the increase in height and diameter, quality and survival of the seedlings. The increase in diameter was 14.71mm and in height 34.88cm. There is a statistical difference in the increase in diameter and height in the evaluation strips, having strip 5 with the greatest increase in diameter and strip 8 with the greatest increase in height. There is a high survival of the plants with 90.5%. It is recommended to carry out maintenance, continue with biometric evaluations and carry out similar plantations with other native forest species in CIEFOR - Puerto Almendra.